Ties that bind and unbind: charting the boundaries of European Union citizenship - Ashley Mantha-Hollands; Jelena Dzankic (Journal of Ethnic and Migration Studies, 2022)
Acquiring or losing European Union (EU) citizenship is contingent on the possession of citizenship of one of the Member States. Since the early 1990s, scholars have debated the unique character of EU citizenship. Remarkably, these debates have paid scarcely any attention to how EU citizenship is (un)recognised through the different conceptions of membership in the 27 countries that make up its boundaries. This article argues that understanding the substance of EU citizenship requires a look into the different domains of citizenship laws in each of the Member States. We present a novel conceptual framework for studying citizenship regimes through four types of citizen-state links: lineage, territory, sponsorship and merit. We find that the disparity among the Member States in who is (un)seen as an EU citizen results from the different ways in which the four types of state-citizen links are articulated in the rules for citizenship acquisition and loss.
Keywords: 300; citizenship; EU citizenship; birthright; naturalisation; revocation